International Journal of the Sociology of Language (De Gruyter Mouton, 1974)
IJSL is dedicated to the development of the sociology of language as a truly international and interdisciplinary field in which various approaches - theoretical and empirical - supplement and complement each other, contributing thereby to the growth of language-related knowledge, applications, values and sensitivities. The journal features topically-focused issues with individual contributions on small languages and small language communities.